Application of time reversal technique in shallow water environment - Jastrzębski, Sławomir (Archives of Acoustics, 2007)
Underwater acoustic communications in shallow water environment is a challenging problemdue to the intersymbol interference caused by time-varying dispersive multipath channel.The paper describes this effect and the passive time reversal technique and its spatial andtemporal focal properties to reduce channel fading and intersymbol interference which causessevere distortions of received communication signals. Recently time reversal technique is amethod introduced to the underwater acoustic communication. In a significant multipath environmentthe time reversal process offers unique opportunity for solving the multipath problemand recovering the original signal at the focus. Communication systems can be divided into incoherentor coherent modulation. In this article coherent underwater acoustic communicationmethod was presented by using passive phase conjugation and 16QAM (quadrature amplitudemodulation) as a modulation method. Presented results confirm the utility of the passive phaseconjugation in shallow water environment to underwater communications.